AN IMMUNOTHERAPEUTIC CONCEPT OF MICROBIAL ANTIGEN APPLICATION IN ATOPY AND DISORDERS ASSOCIATED WITH FACULTATIVE MICROFLORA, AS EXEMPLIFIED BY A POLYCOMPONENT IMMUNOVAC VP4 VACCINE - N. B. Egorova; E. A. Kurbatova (Медицинская иммунология)
Abstract. Immunomodulating drugs play an important role in therapy and prevention of numeous diseases associated with altered immune functions. Immunomodulators of bacterial origin are the most active ones, serving as a basis for design of therapeutic vaccines that are capable of stimulating antigen-specific response, along with nonspecific actions. The Immunovac VP4 poly-component vaccine is among such preparations, being a potent activator of innate immunity and showing protective activities against a number of facultative pathogens. In present review, the data are summarized that concern therapeutic effects of Immunovac VP4 in various disorders (lung abscess, chronic bronchitis, bronchial asthma, atopic dermatitis, pyodermia, herpes, acute respiratory infections). In all cases, high clinical effect was registered, i.e., decrease in number and severity of relapses, decreased dosage/number of medical drugs applied, prolongation of remission states, and transition to less severe clinical forms. The therapeutic effect is accompanied by sufficient positive dynamics of immunological parameters, e.g., phagocytic activity of macrophages, increase in lymphocytes bearing CD4, CD8, CD16, CD72, CD21 markers, enhanced IFNγ and IFNα production, correction of Ig synthesis, increased antibody titers and affinity. Analysis of data from strictly controlled studies performed in limited clinical samples, has shown a number of general regularities for common effects of microbial antigens in various disorders including allergic diseases.